Traditional Costume of Ethnic Groups of Yunnan Province in the Genre and Thematic Repertoire of the Yunnan School of Painting - Zhang, Heng (HUDPROM: The Ukrainian Art and Design Journal, 2025)
The article examines the artistic representation of traditional ethnic costume of Yunnan Province within the context of modern painting practices of the Yunnan school. Particular attention is given to two aspects of its genre and thematic repertoire of the school. The first concerns the identification of regional ethnic features through costume, achieved by combining the genres of landscape and narrative painting. The second involves the integration of ethnic imagery into portraiture as an expressive means, which, in the author’s view, contributes to revealing the inner dramaturgy of the pictorial text. The study concludes that by actualizing the distinctive features of the landscape and traditional culture of the region, the Yunnan School presents a rich spectrum of imagery situated at the intersection of tradition and modernity. Traditional costume emerges as a developed visual language, employed both in portraiture and in the transformation of landscape and narrative painting. While such use of costume is conventional in portraiture, the involvement of the landscape as a “cultural hero” with its own set of ethnic markers represents a defining characteristic of the Yunnan School. The synthesis of landscape and subject painting allows artists such as Bai Shi, Sun Jingbo and Yao Zhonghua to create a full and comprehensive panorama of the cultural diversity of the province. At the same time, the incorporation of traditional costume into various artistic strategies and individual styles enriches the regional identity and ethnic specificity of the Yunnan School’s distinctive “strong color” painting.